Economic Impacts of Farmers Cooperatives in Nepal: A Study of Uthan Farmers’ Cooperatives Limited Kalika-8 Chitwan - Dhakal, Chandra Prasad (NUTA Journal, 2022)
The study analyzes the economic impactsof Uthan Farmers'CooperativeLimited in term of financial viability like employment, income and saving. The study explores the impacts in the context of Uthan Farmers' Cooperative Limited (UFCL), Kalika municipality ward no 8 Chitwan. Main objective of the study is to find out the perception of users group of the cooperative on economic impacts like employment, saving and income. Qualitative research design is followed and completed the study. Findings and conclusion of the study is based on primary data collected from the field by interview questions and observation checklist. Members of the cooperative have both positive and negative experiences on the activities of the cooperative ruing in study area (Kalika municipality ward no 8, Chitwan) playing role to bring impacts on the economic aspects of the members.